LITERATUR REVIEW : HUBUNGAN KELELAHAN KERJA (FATIGUE) DENGAN KECELAKAAN KERJA DI INDUSTRI PERTAMBANGAN - Devanda Faiqh Albyn; Rizky Gilang Romadhon (PT Nuansa Fajar Cemerlang, 2026)
Work fatigue is closely related to the increased risk of workplace accidents in the mining industry. This industry is known to have a high risk of accidents, and one of the main contributing factors is worker fatigue due to high workloads, long working hours, and extreme work environments. The study of fatigue in the mining industry is crucial for several key reasons. The main objective of this study is to enrich the understanding of fatigue risk factors, encourage the development of mitigation strategies, and improve the safety, health, and well-being of workers in the mining industry. The existing literature was reviewed to identify and analyze the impact of work fatigue on worker performance and health in the mining industry. This study used the Narrative Literature Review method with data collection conducted through a literature search using academic journals using relevant keywords, within the time period of 2020 to 2025. The researcher analyzed several literatures and then summarized the results obtained, the analysis in the form of a table that includes 8 components such as title, Year of Research, Journal Source, Research Title, Author, Problem Identification, Research Method, and research results. Quoted from 21 journals used are the most recent journals within the last 5 years and state that most of the journals state that fatigue is the main cause of workplace accidents. The conclusion and suggestion in this study is the urgency of implementing a fatigue management system (FMS) and monitoring worker conditions regularly as a strategic step to reduce the risk of accidents due to fatigue. It can be concluded that fatigue can increase the risk of accidents in the workplace, both those resulting in minor and fatal injuries.